Systematic Review & Meta-Analysis Triple Inhaler Therapy Outperforms Dual Therapy in Moderate to Severe COPD: A Meta-Analysis of 11,477 Patients from 4 Randomized Controlled Trials Shows Improved Lung Function, Reduced Exacerbations, and Comparable Safety Profile - Albab, Chabib Fachry; Habibah, Almas Talida; Wulandhari; Murteza, Faiq; Mas'udi, Achmad Fayyad (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) continues to be one of the most prevalent health conditions globally. Treatment strategies for COPD are often tailored to disease severity, beginning with single therapy and advancing to dual or triple therapy as needed. However, limited randomized controlled trials (RCTs) have explored the comparative impact of dual and triple inhaler therapies on clinical outcomes and exacerbation frequencies. Our meta-analysis aims to evaluate the effectiveness and safety of triple and double medication in moderate and severe COPD patients. Material and Methods: A comprehensive exploration of databases was conducted to identify RCTs comparing triple and dual inhaler therapies. For binary outcomes, the pooled RR or OR was calculated; we also used weighted MD to analyze continuous outcomes, both with high CI (95%). Results: The meta-analysis included four RCTs involving 13,574 patients, of whom 67.92% were male. Triple inhaler therapy proves lung function improvements significantly, evidenced by an increase in FEV1 (MD: 0.06; 95% CI: 0.01–0.11; p=0.02). It showed significant association with a exacerbations reduction in both moderate and severe one (RR: 0.76; 95% CI: 0.72–0.81; p<0.000001). No notable differences in adverse events were observed between combination of triple and double medication (OR: 0.99; 95% CI: 0.90–1.10; p=0.85). Conclusion: Triple inhaler medication proves more effective than double medication in moderate and severe COPD patients, enhancing lung function and lowering exacerbation rates without a significant increase in adverse effects.